2010
DOI: 10.4103/0378-6323.72464
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of narrow-band ultraviolet B phototherapy alone and its combination with topical 8-methoxypsoralen in psoriasis

Abstract: To conclude, topical 8-MOP enhances the therapeutic effects of NBUVB therapy without increasing the incidence of adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Recently, Jain et al . compared the combination of psoralen‐NBUVB with NBUVB alone in psoriasis; the number of treatment sessions and cumulative doses were lower with the combination therapy, although not to a significant level .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Recently, Jain et al . compared the combination of psoralen‐NBUVB with NBUVB alone in psoriasis; the number of treatment sessions and cumulative doses were lower with the combination therapy, although not to a significant level .…”
Section: Discussionmentioning
confidence: 96%
“…They showed 58.6% decrease in total score after nine sessions in contrast to 37.7% in the control group (P = 0.043).They concluded that combination of 8MOP with NBUVB increased the rate of improvement in treatment-resistant lesions of psoriasis (7). Recently, Jain et al compared the combination of psoralen-NBUVB with NBUVB alone in psoriasis; the number of treatment sessions and cumulative doses were lower with the combination therapy, although not to a significant level (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sin embargo, no hay datos clínicos sobre el desarrollo de carcinogénesis en humanos. Por lo anterior, se recomienda el uso prudente en casos de psoriasis [5][6][7][8][9][10][11][12][13][14][15][16] .…”
Section: Radiación Uvb E Inhibidores De La Calcineurinaunclassified